Phenotypic and functional analysis of γδ T cells in the pathogenesis of human T-cell lymphotropic virus type 1 infection - Ruggieri, Matias; Ducasa, Nicolás; Juraske, Claudia; Polo, Virginia Gonzalez; Berini, Carolina; Quiroga, Maria Florencia; Christopoulos, Petros; Minguet, Susana; Biglione, Mirna; Schamel, Wolfgang W. (Frontiers in Immunology, 2022)
The human T-cell leukemia virus type 1 (HTLV-1) is the cause of serious malignant and inflammatory diseases, including adult T-cell leukemia and lymphoma and tropical spastic paraparesis. The potential protective role of γδ T cells in HTLV-1 infection remains unclear. Here, demonstrate that there is a decrease in the amount of Vγ9Vδ2 T cells in patients with HTLV-1, especially in those with HTLV-1 associated pathologies. This suggests that γδ T cells could be involved in controlling the virus. Indeed, we found that Vγ9Vδ2 T cells, expanded from non-infected individuals, can kill cells expressing the viral proteins HBZ and Tax and this phenotype is reversed in the presence of mevastatin. Cytotoxicity by Vγ9Vδ2 T cells was not associated with an increase of INF-γ production. In sharp contrast, killing by NK cells was reduced by Tax expression. Thus, our study provides initial evidence for a potential protective role of Vγ9Vδ2 T cells against HTLV-1 infection. Therapeutic exploitation of these insights is feasible with current technologies of T-cell therapies and could provide novel tools to prevent and treat HTLV-1-associated malignancies and neurologic complications.